Product Innovation Practices of Ulos-Based Bandanas in the Creative Economy Value Chain - Marshanda Siburian; Cheresentia Situmorang; Era Sulastri Hutasoit; Stevani Nababan; Putri Kemala Dewi Lubis (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2026)
This study analyzes the associations of competence, work motivation, and organizational culture with employee performance in a facility services company (PT Esefa Semesta Facility), where job demands require strict compliance with established standard operating procedures, consistent field service delivery, and adaptation to client needs. The study employed a quantitative explanatory (cross-sectional) design using a structured questionnaire administered to all employees through saturated sampling (n = 62). Data were analyzed using multiple linear regression in SPSS 26 after instrument and assumption testing. The results show that competence (B = 0.331; p = 0.010), work motivation (B = 0.284; p = 0.020), and organizational culture (B = 0.388; p = 0.010) are positively and significantly associated with employee performance. Simultaneously, the overall model is significant (F = 102.080; p < 0.001) and explains a substantial proportion of variance (Adjusted R² = 0.833). These findings suggest that strengthening job-relevant competencies, sustaining work motivation, and fostering an adaptive work culture are practical managerial levers to reduce service variability and improve performance in facility services operations, while causal inference remains limited due to the cross-sectional design.